Proyección de demanda: ¡este problema no es normal! (2015)
This case discusses a problem that may arise when using a semi-logarithmic linear model to forecast the demand of a given product. This problem is presented using the discussion that emerges in a company that is looking for an approach to forecast the demand of its leading product. The reader faces the challenge of deciding which approach is adequate to the problem.